Production of Calcium Nitrate Fertilizer from Calcium Hydroxide Waste: Effects of Reaction Temperature and Nitric Acid Concentration - Devina Anindya Sabella; Dyah Ayu Nyata Ningrum; Sintha Soraya Santi; Suprihatin; Caecilia Pujiastuti (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Calcium hydroxide (Ca(OH)?) waste generated from the acetylene gas industry contains a high calcium content and has potential to be utilized as an alternative raw material for calcium nitrate fertilizer production. This study presents a novel approach for the valorization of Ca(OH)? industrial waste into a value-added calcium nitrate fertilizer through a reaction and crystallization process. The effects of reaction temperature and nitric acid concentration on calcium nitrate production were investigated. The Ca(OH)? waste was initially reduced to a particle size of 100 mesh, then reacted with nitric acid at concentrations of 1, 1.25, 1.5, 1.75, and 2 N and at reaction temperatures of 50, 60, 70, 80, and 90°C for 1 hour. The obtained calcium nitrate solution was filtered, neutralized using 25% NH?OH until pH 7, and crystallized at 150°C to obtain calcium nitrate crystals. The raw material was characterized using X-ray fluorescence (XRF), while the calcium nitrate product was analyzed using inductively coupled plasma (ICP), spectrophotometry, and yield calculation. The XRF analysis showed that Ca(OH)? waste contained 98.71% calcium. At a reaction temperature of 70°C and a nitric acid concentration of 1.5 N, calcium nitrate was successfully produced with the highest calcium (Ca) and nitrogen (N) content of 21.91% and 16.74%, respectively, and produced a yield of 69.564%, which is in accordance with the Indonesian National Standard (SNI 02-2806-1992) for calcium nitrate fertilizer, which stipulates a Ca content of 19–22% and an N content of 15.5%. This study was conducted without experimental replication; therefore, statistical significance analysis was not performed. The findings demonstrate that Ca(OH)? waste from the acetylene industry can be effectively valorized into calcium nitrate fertilizer, providing an alternative strategy for industrial waste utilization and supporting circular economy principles. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action